African swine fever control in Ibadan, Nigeria: problems, needs and veterinary extension opportunities (2008)
African swine fever (ASF) is a widely discussed disease in Ibadan, Nigeria, where high mortality losses occurred in outbreaks in the city between 2001-2006. To study the level to which ASF containment technologies were adopted and factors associated with adoption behavior, a sample of 60 pig farmers was selected from six local government areas in and near Ibadan. Essential data were collected using a questionnaire. Assessment criteria in forms of frequency, percentage, mean and product moment correlation coefficient were calculated. Results showed that the majority of pig farmers did not adopt ASF biocontainment technologies, since 86.7% (52/60) were at a low level of adoption behavior, 10% (6/60) at a medium level, and 3.3% (2/60) at a high level. A farmer’s income from piggery, knowledge of biocontainment technologies, and frequency of extension contact had positive and highly significant relationships (r 0.787) on levels of adoption. Specific needs and emerging opportunities for farmer participatory learning were indicated. It was recommended that Pig Farmers Association should constitute Farmer Field Schools, where the State Ministry of Agriculture and Natural Resources (MANR) would be involved in production of ASF virus-free pigs, and the current services by University-based officers to the early detection of pigs infected with the ASF virus will be optimized